The Effectiveness of Cumin as Natural Antioxidant to Improve Rumen Ecology of Mastitis Dairy Cows - Nurdin, E; Arief, Arief (ANIMAL PRODUCTION, 2009)
The researchÂ  was on the effect of supplementation of natural antioxidant (Cuminum cyminum) to improve rumen ecology of Mastitis Dairy Cows and improved milk production. This research was in-vitro treatments and using rumen fluids of Holstein dairy cows with mastitis condition. They were fed diets supplemented with various levels of a natural antioxidant ( A; 0 ppm; B: 500 ppm; C: 1000 ppm and D: 1500 ppm).Â  Total of Rumen Bactery, pH, NH3, acetate acid, propionate acid and butirate acid were determined. The design of this experiment was used Randomized Design. The collected data were analyzed by Multiple Analysis of Variance. While the difference between the treatment effects was tested using Duncanâs Multiple Range Test. The results showed that supplementation ofÂ Â  1 000 ppm of Cuminum cyminum caused increase of population bactery, Acetic acid and Propionic acidÂ  and decrease of NH3 concentration (P<0.05). TheyÂ  are not effect for milk acidity (P>0.05). Our conclusion, the level 1 000 ppm of Cuminum cyminum improve to good condition of rumen ecology. It showed to increase bactery rumen (66.02%), decrease NH3 concentration (7.58%), increase asetic acid (49.91%) and propionic acid (29.94 %).Â  Condition of pH rumen is showed in normal condition. (Animal Production 11(3): 160-164 (2009)Â Key Words: Cumminum cyminum, anti-oxidant, rumen ecology, mastitis, dairy cows